(untitled) (Research, Society and Development, 2020)
This work aimed to evaluate the potassium phosphite-based commercial product, Phytogard®, as a complementary tool for the management of gummosis in citrus. Seedlings of tangerine ‘Sunki’ were sprayed at concentrations 0; 0.5; 2 and 5 mL L-1 of Phytogard® and subsequently inoculated with zoospores of Phytophthora nicotianae. The disease incidence was reduced by 84% in plants sprayed at the concentration 0.5 mL L-1 and the plants sprayed at concentrations of 2 and 5 mL L-1 showed zero disease incidence. There was increased an production of fresh matter of shoot and roots in plants sprayed and inoculated with the pathogen compared to unsprayed plants. Plants sprayed with Phytogard® and inoculated with the pathogen showed lower values for total phenols, enzyme activity for phenylalanine ammonia-lyase and peroxidase and for total protein content in root tissues compared to non-inoculated plants. There was higher activity of the enzyme β 1.3-glucanase in root tissues of plants inoculated with the pathogen that received the product at the concentration of 2 mL L-1. The results of this study showed that the potassium phosphite-based product Phytogard® has potential for the control of Phytophthora nicotianae in seedlings of tangerine ‘Sunki’. However, it is not possible to conclude that this control occurs through resistance induction.